A Proteomic Analysis Indicates That Oxidative Stress Is the Common Feature Triggering Antibiotic Production in Streptomyces coelicolor and in the pptA Mutant of Streptomyces lividans - Lejeune, Clara; Sago, Laila; Cornu, David; Redeker, Virginie; Virolle, Marie-Joelle (Frontiers in Microbiology, 2022)
In most Streptomyces species, antibiotic production is triggered in phosphate limitation and repressed in phosphate proficiency. However, the model strain, Streptomyces coelicolor, escapes this general rule and produces actinorhoddin (ACT), a polyketide antibiotic, even more abundantly in phosphate proficiency than in phosphate limitation. ACT was shown to bear “anti-oxidant” properties suggesting that its biosynthesis is triggered by oxidative stress. Interestingly, Streptomyces lividans, a strain closely related to S. coelicolor, does not produce ACT in any phosphate condition whereas its pptA/sco4144 mutant produces ACT but only in phosphate limitation. In order to define the potentially common features of the ACT producing strains, these three strains were grown in condition of low and high phosphate availability, and a comparative quantitative analysis of their proteomes was carried out. The abundance of proteins of numerous pathways differed greatly between S. coelicolor and the S. lividans strains, especially those of central carbon metabolism and respiration. S. coelicolor is characterized by the high abundance of the complex I of the respiratory chain thought to generate reactive oxygen/nitrogen species and by a weak glycolytic activity causing a low carbon flux through the Pentose Phosphate Pathway resulting into the low generation of NADPH, a co-factor of thioredoxin reductases necessary to combat oxidative stress. Oxidative stress is thus predicted to be high in S. coelicolor. In contrast, the S. lividans strains had rather similar proteins abundance for most pathways except for the transhydrogenases SCO7622-23, involved in the conversion of NADPH into NADH. The poor abundance of these enzymes in the pptA mutant suggested a deficit in NADPH. Indeed, PptA is an accessory protein forcing polyphosphate into a conformation allowing their efficient use by various enzymes taking polyphosphate as a donor of phosphate and energy, including the ATP/Polyphosphate-dependent NAD kinase SCO1781. In phosphate limitation, this enzyme would mainly use polyphosphate to phosphorylate NAD into NADP, but this phosphorylation would be inefficient in the pptA mutant resulting in low NADP(H) levels and thus high oxidative stress. Altogether, our results indicated that high oxidative stress is the common feature triggering ACT biosynthesis in S. coelicolor and in the pptA mutant of S. lividans.